Neural Software Analysis. - PRADEL, MICHAEL; CHANDRA, SATISH (Communications of the ACM, 2022)
The article discusses developments in neural software analysis. It examines how neural software analysis assists in the creation of software development tools, how it approaches fuzzy information including natural language, and challenging software development problems.